New approach for the transformation of metallic waste into nanostructured Fe3O4 and SnO2-Fe3O4 heterostructure and their application in treatment of organic pollutant. (15th March 2019) - Devi, Mayanglambam Manolata; Sunaina,; Singh, Harish; Kaur, Kuljeet; Gupta, Ankita; das, Anirban; Nishanthi, S.T.; Bera, Chandan; Ganguli, Ashok Kumar; Jha, Menaka
Graphical abstract: Highlights: Design of new process of conversion of metallic waste to SnO2 :Fe3 O4 nanocomposite. Tuning of the composition of nanocomposite have been carried out. SnO2 :Fe3 O4 nanocomposite act as an efficient photocatalyst in UV and Visible range. Abstract: Appropriate recycling of waste to reusable materials is much sought after in the scientific community to control the incessant rising pollution in environment due to insufficient management of waste materials. To address this issue, efforts were directed to obtain SnO2 -Fe3 O4 nanocomposites from scrap tin plated steel and the use of these composites for the degradation of organic pollutant. We have demonstrated a novel, efficient and facile hydrometallurgy approach for the extraction of iron from waste tin plated steel containers found in plenty in the common waste generated in society. The extracted iron has further been utilized for the preparation of SnO2 :Fe3 O4 nanocomposites with different compositions (SnO2 :Fe3 O4 ratio of 93.2:6.8, 85:15, 58:42 and 40:60) using hydrothermal route. The photocatalytic activities of nanocomposite were determined spectroscopically using Rhodamine-B (RhB) as a model dye. Our results indicate that among all the composites with SnO2 (85%):Fe3 O4 (15%) exhibits the best photocatalytic efficiency under UV light whereas the composition of SnO2 (93.2%):Fe3 O4 (6.28%) is the most efficient in visible light. The above visible light efficiency was supported by density functional theory (DFT) studies which suggest a small amount of pure Fe is present at the Sn sites in the nanocomposite, leading to the reduction in the band gap of the nanocomposite and resulting in absorption in the visible range. Thus, in the present study, we have shown a process of conversion of waste to nanomaterials and its utilization for treatment of organic pollutants.